“БИСМИЛЛАҲ” ТАФСИРИ - Ишаев, Ж.Э. (SCIENCE and SOCIETY, 2021)
This article is about the science of Kur’an. It deals with the interpretation of Basmala. However, information about its quality is given. Data are obtained from reliable sources. Different narrations are compared.